Guillain-Barre Syndrome following Intracranial Surgery for Traumatic Intracerebral Hemorrhage - Uddin, Mohammad Najim; Aziz, Mohammad Faisal; Das, Swarup (Journal of Chittagong Medical College Teachers' Association, 2022)
Background: A case of Guillain-Barre Syndrome (GBS) with respiratory failure following craniotomy for post traumatic intracerebral bleed is described. The association of Guillain-Barre syndrome with head injury is not well recognized and a possible immunological association may be existing. The objective of our study is to describe clinical and Neurophysiological findings of GBS after trauma and Surgery. Case Presentation: On 24th August 2022, a 45 years old Bangladeshi male brought by his family to Emergency Department of Evercare Hospital Chattogram. During evaluation, family added that he sustained a head injury on 4th August 2022 after bike accident and was admitted to private hospital that day, where Computed Tomographic (CT) brain scan revealed right fronto-parietal contusions and a right subdural hematoma. He was underwent Craniotomy on the same day, followed by uneventful ICU stay, improved rapidly in cabin and was discharged on 17th August 2022. On 19th August 2022, he again become drowsy and rapidly progressive weakness of all 4 limbs. On 24th August he was intubated in hospital emergency for respiratory failure. A repeat CT scan showed no interval changes, Cerebrospinal fluid (CSF) and neurophysiology studies were suggestive of GBS. Patient was extubated after Intravenous Immunoglobulin therapy (IVIG). Conclusion: GBS may be considered in patients with progressive muscle weakness after surgery and which improve with timely treatment with IVIG. JCMCTA 2022 ; 33 (2) : 136-139